Impacts of tacrolimus and glucocorticoids on peripheral blood T and B lymphocyte subsets in myasthenia gravis - Wu, Xuan; Chen, Wei; Song, Huanhuan; Xu, Guorong (Frontiers in Immunology, 2025)
BackgroundThis study aimed to investigate the impact of tacrolimus on peripheral T and B lymphocyte subsets in myasthenia gravis (MG) patients compared to glucocorticoid treatment.MethodsThis study retrospectively included MG patients at the First Affiliated Hospital of Fujian Medical University between January 2021 and December 2024. Patients were grouped based on immunotherapy received: tacrolimus (TAC) or glucocorticoids (GC). Peripheral blood samples were assessed for T lymphocyte subsets (CD3+, CD4+, CD8+) and B lymphocyte subsets (CD19+), alongside clinical parameters.ResultsA total of 46 MG patients were included, with 23 patients in each treatment group. Baseline characteristics, including sex, age at onset, antibody profile, and thymic pathology, were comparable between the two groups (all P > 0.05), except for a significantly higher proportion of generalized MG in the TAC group (P = 0.017). Following treatment, the TAC group demonstrated a significantly lower absolute count of CD3+CD4+ T cells compared to the GC group (663.4 ± 345.5 × 106/L vs. 952.5 ± 513.9 × 106/L, P = 0.030). Additionally, the percentage of peripheral B cells in the tacrolimus group decreased significantly after treatment (from 11.8 ± 4.7% to 9.4 ± 4.4%, P = 0.006). In contrast, patients treated with glucocorticoids showed significant post-treatment increases in the absolute counts of CD3+, CD3+CD4+, and CD3+CD8+ T cells (all P = 0.001).ConclusionCompared with patients receiving glucocorticoid therapy, those treated with tacrolimus exhibited significantly lower levels of peripheral CD3+CD4+ T cells after treatment. These findings provide insight into the differential immunomodulatory effects of these therapies in MG.